Multi-scale burned area mapping in tallgrass prairie using in SITU spectrometry and satellite imagery. - Mohler, Rhett L. (Kansas State University, 2011)
Prescribed burning in tallgrass prairie affects a wide range of human and natural systems. Consequently, managing this biome based on sound science, and with the concerns of all stakeholders taken into account, requires a method for mapping burned areas. In order to devise such a method, many different spectral ranges and spectral indices were tested for their ability to differentiate burned from unburned areas at both the field and satellite scales. Those bands and/or indices that performed well, as well as two different classification techniques and two different satellite-based sensors, were tested in order to come up with the best combination of band/index, classification technique, and sensor for mapping burned areas in tallgrass prairie. The ideal method used both the red and near-infrared spectral regions, used imagery at a spatial resolution of at least 250 m, used satellite imagery with daily temporal resolution, and used pixel-based classification techniques rather than object-based techniques. Using this method, burned area maps were generated for the Flint Hills for every year from 2000-2010, creating a fire history of the region during that time period. These maps were compared to active fire and burned area products, and these products were found to underestimate burned areas in tallgrass prairie.
Keywords: Tallgrass prairie; Burn mapping; Satellite imagery; Geography (0366)